ABS (Acrylonitrile Butadiene Styrene) alloy material and preparation method and application thereof

By adding ASA glue powder, phosphorus flame retardant, nitrogen flame retardant and heteropolyate to ABS resin, the composition of ABS alloy material is optimized, and the flame retardant and resistance of existing ABS materials is solved. The shortcomings in solvent performance have achieved halogen-free V0 flame retardant grade, good mechanical properties and solvent resistance of thin-walled ABS alloy materials.

CN119463407AActive Publication Date: 2025-02-18KINGFA SCI & TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411739565.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The existing ABS materials have problems with insufficient environmental protection and solvent resistance in flame retardant modification, and it is difficult to meet the high flame retardant and solvent resistance requirements of thin-walled products.

Method used

By adding ASA glue powder, phosphorus flame retardant, nitrogen flame retardant and heteropolyate to the ABS resin, the composition of ABS alloy material is optimized to achieve halogen-free V0 flame retardant grade and good solvent resistance .

Benefits of technology

The halogen-free V0 flame retardant grade of thin-walled ABS alloy material has been realized, and its mechanical properties and solvent resistance are improved, and it meets the 2.0mm V0 flame retardant grade, modulus of 1623MPa, impact strength of 14.2kJ/m2 and ice resistance. The requirement for acetic acid cracking time is above 17 minutes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005162318020000061
    Figure BDA0005162318020000061
  • Figure BDA0005162318020000071
    Figure BDA0005162318020000071
  • Figure BDA0005162318020000072
    Figure BDA0005162318020000072
Patent Text Reader

Abstract

The invention discloses an ABS (Acrylonitrile Butadiene Styrene) alloy material as well as a preparation method and application thereof, and belongs to the technical field of high polymer materials. The ABS alloy material provided by the invention is prepared from the following components in parts by mass: 58 to 82 parts of ABS resin, 18 to 42 parts of ASA rubber powder, 6 to 14 parts of phosphorus flame retardant, 5 to 11 parts of nitrogen flame retardant, 5 to 11 parts of heteropolyacid salt and 2 to 8 parts of compatilizer. According to the ABS alloy material provided by the invention, components in proper parts by mass are selected and matched with one another, so that a thin-wall product prepared from the ABS alloy material has a V0 flame retardant grade, and also has good rigidity-toughness balance and excellent solvent resistance. In addition, the preparation method of the ABS alloy provided by the invention is simple to operate and beneficial to actual production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to an ABS alloy material and a preparation method and application thereof. Background Art

[0002] ABS, or acrylonitrile-butadiene-styrene terpolymer, is a general-purpose plastic that combines the characteristics of rigidity and toughness balance, high gloss, easy processing and dimensional stability. It is widely used in home appliances, office equipment, and electronic and electrical industries. However, the oxygen index of ABS resin is only about 18, which is a flammable material. It needs to be flame-retardant modified before it can be used in electrical-related products, which greatly limits the application of ABS.

[0003] At present, the flame retardant modification technology of ABS is very mature. The most common method is to add bromine antimony flame retardant to ABS to prepare flame retardant ABS; however, this method adds halogen-containing flame retardant, which is an environmentally unfriendly solution and does not conform to the development trend of ABS. A Chinese patent (CN 118406345 A) discloses a flame retardant ABS composite material and a preparation method thereof. The scheme adopts a coated modified phosphorus-nitrogen composite flame retardant to achieve a V0 halogen-free flame retardant grade. However, the red phosphorus flame retardant used therein has certain toxicity, and there is a risk of fire in the production process. In addition, halogen-free V0 flame retardancy can also be achieved by blending PC and ABS and adding phosphate flame retardant. However, the solvent resistance of halogen-free flame retardant PC / ABS is poor and cannot be used in products that require solvent resistance.

[0004] In summary, flame-retardant ABS still has shortcomings such as environmental protection and solvent resistance. It is of great significance to develop environmentally friendly and solvent-resistant halogen-free V0 flame-retardant ABS materials. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide an environmentally friendly ABS alloy material and a preparation method and application thereof, which is used for the preparation of thin-walled products (wall thickness ≤ 2 mm) and has excellent flame retardancy, excellent solvent resistance and good mechanical properties.

[0006] To achieve the above object, in a first aspect of the present invention, the present invention provides an ABS alloy material, wherein the ABS alloy material comprises the following components in parts by weight:

[0007] 58-82 parts of ABS resin, 18-42 parts of ASA rubber powder, 6-14 parts of phosphorus flame retardant, 5-11 parts of nitrogen flame retardant, 5-11 parts of heteropoly acid salt, and 2-8 parts of compatibilizer.

[0008] The ABS alloy material provided by the present invention selects appropriate components by mass to cooperate with each other, so that the ABS alloy material can be prepared into a thin-walled product with a V0 flame retardant grade and also has good rigidity-toughness balance and excellent solvent resistance.

[0009] Specifically, the present invention selects to add ASA rubber powder, which can not only provide a halogen-free flame-retardant carbon source, and work together with flame retardants and heteropolyacid salts to improve the flame retardancy of the product, but also interact with ABS resin to effectively toughen the system, improve the mechanical properties of the product and the solvent resistance of the product. The addition of heteropolyacid salts, on the one hand, as an acid source, has a strong dehydration ability and can cover the surface of the burning material to improve the flame retardant effect of the product; at the same time, it can also cooperate with phosphorus-based flame retardants and nitrogen-based flame retardants to further improve the halogen-free flame retardant effect of the product, so that the product can also achieve a halogen-free V0 flame retardant grade in a thin-walled state; and the addition of heteropolyacid salts will not damage the mechanical properties of the product on the basis of improving the flame retardancy, which is conducive to ensuring the good mechanical properties of the product. On the other hand, because heteropolyacid salts have extremely large anions and cations, they can interact strongly with solvents, adsorb solvents, weaken the effects of solvents and resin matrixes, and avoid solvent-induced cracking, thereby improving the overall solvent resistance.

[0010] Exemplarily, the solvent in the solvent resistance performance includes at least one of acetic acid, ethanol, and edible oil.

[0011] Exemplarily, the ABS resin may be any point value or any two point range value between 58-82 parts, such as 60-80 parts, or 58 parts, 60 parts, 62 parts, 65 parts, 68 parts, 70 parts, 72 parts, 75 parts, 78 parts, 80 parts, 82 parts, etc.; the ASA rubber powder may be any point value or any two point range value between 18-42 parts, such as 20-40 parts, or 18 parts, 20 parts, 23 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts, 38 parts, 40 parts, 42 parts, etc.; the phosphorus-based flame retardant may be any point value or any two point range value between 6-14 parts, such as 7-13 parts, Or it can be 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, etc.; the nitrogen-based flame retardant can be any point value or any two-point range value between 5-11 parts, for example, it can be 6-10 parts, or it can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, etc.; the heteropolyacid salt can be any point value or any two-point range value between 5-11 parts, for example, it can be 6-10 parts, or it can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, etc.; the compatibilizer can be any point value or any two-point range value between 2-8 parts, for example, 3-7 parts, or it can be 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, etc.

[0012] In the ABS alloy material, the mass percentage of ABS resin is ≥40%.

[0013] Preferably, in the ABS alloy material, the mass percentage of ABS resin is 48-60%.

[0014] As a preferred embodiment of the ABS alloy material of the present invention, the mass ratio of the ABS resin to the ASA rubber powder is 1:(0.2-0.7).

[0015] Exemplarily, the mass ratio of the ABS resin to the ASA rubber powder may be any point value or any range value between 1:(0.2-0.7), such as 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, etc.

[0016] The present invention has found that the mass ratio between ABS resin and ASA rubber powder will affect the mechanical properties, flame retardant properties and solvent resistance of the product. When the mass ratio of ABS resin and ASA rubber powder is further selected to be 1: (0.2-0.7), the comprehensive performance of the obtained product is better.

[0017] Preferably, the mass ratio of the ABS resin to the ASA rubber powder is 1:(0.33-0.5).

[0018] As a preferred embodiment of the ABS alloy material of the present invention, the heteropolyacid salt includes at least one of dodecamolybdenum phosphate, dodecatungstate phosphate, dodecamolybdenum silicate and dodecatungstate silicate.

[0019] Preferably, the heteropolyacid salt includes dodecatungstate phosphate and dodecatomolybdate phosphate.

[0020] More preferably, the heteropolyacid salt comprises dodecatungstophosphate.

[0021] Exemplarily, the dodecatungsten phosphate includes at least one of sodium dodecatungsten phosphate, magnesium dodecatungsten phosphate, iron dodecatungsten phosphate, aluminum dodecatungsten phosphate, chromium dodecatungsten phosphate, zinc dodecatungsten phosphate, rhodium dodecatungsten phosphate, and copper dodecatungsten phosphate.

[0022] The present invention has found that there are differences in the types of heteropolyacid salts themselves and in their interactions with phosphorus-based flame retardants and nitrogen-based flame retardants. When the type of heteropolyacid salt is further selected as the above-mentioned category, especially dodecatungstophosphate, the flame retardancy of the obtained product is better, and a thin-walled product (thickness ≤ 2 mm) with a V0 flame retardant grade can be achieved, and the flame retardant effect is better, and the mechanical properties and solvent resistance of the obtained product are better.

[0023] As a preferred embodiment of the ABS alloy material of the present invention, the compatibilizer includes at least one of ABS grafted with maleic anhydride, styrene-maleic anhydride grafted product, maleic anhydride grafted with SEBS, and stearic acid alcohol ester.

[0024] Preferably, the compatibilizer comprises ABS grafted with maleic anhydride.

[0025] The present invention has found that the type of compatibilizer affects the compatibility between the components, thereby affecting the effect of the product. When the compatibilizer is further selected to be the above type, especially ABS grafted with maleic anhydride, the comprehensive performance of the obtained product is better.

[0026] As a preferred embodiment of the ABS alloy material of the present invention, the rubber mass percentage of the ABS resin is 15-30%.

[0027] It should be noted that the rubber mass percentage of ABS resin is determined by the dissolution precipitation method. The dissolution precipitation method is specifically: the san phase and the styrene phase are dissolved by an organic solvent (such as dichloromethane), while butadiene as the rubber phase is insoluble in the organic solvent, so as to separate the phases, and the butadiene (rubber) content is calculated after drying.

[0028] Exemplarily, the rubber mass percentage of the ABS resin can be any point value or any two point range value between 15-30%, for example, it can be 18-28%, or it can be 15%, 17%, 19%, 20%, 22%, 24%, 26%, 28%, 30%, etc.

[0029] Preferably, the rubber mass percentage of the ABS resin is 22-24%.

[0030] The present invention has found that when the rubber mass percentage of the ABS resin is 15-30%, especially 22-24%, the comprehensive effect of the obtained product is better.

[0031] As a preferred embodiment of the ABS alloy material of the present invention, the phosphorus-based flame retardant includes at least one of bisphenol A-bis(diphenyl phosphate), triphenyl phosphate, and phenylene tetraphenyl bisphosphate.

[0032] As a preferred embodiment of the ABS alloy material of the present invention, the nitrogen-based flame retardant includes at least one of melamine urate and dicyandiamide.

[0033] The present invention has no special requirements for the ASA rubber powder, and also has no special requirements for the acrylate content in the ASA rubber powder. For example, the acrylate content in the ASA rubber powder can be any point value or any two point range values ​​between 50-70w.t.%.

[0034] As a preferred embodiment of the ABS alloy material of the present invention, the ABS alloy material further comprises 0.1-1 parts of an antioxidant and 0.1-1 parts of a lubricant.

[0035] Exemplarily, the antioxidant includes at least one of a hindered phenol antioxidant, a hindered amine antioxidant, and a phosphite antioxidant.

[0036] Exemplarily, the lubricant includes at least one of a stearic acid amide lubricant and a zinc stearate lubricant.

[0037] In a second aspect of the present invention, the present invention further provides a method for preparing the ABS alloy material, the method comprising the following steps: mixing the components and melt-extruding them to obtain the ABS alloy material.

[0038] As a preferred embodiment of the preparation method of the present invention, the parameters of the twin-screw extruder are: the aspect ratio of the twin-screw extruder is (36-40):1, the screw speed is 250-300rpm, and the extrusion temperature is 190-200°C.

[0039] In the third aspect of the present invention, the present invention also provides the application of the ABS alloy material in the field of household appliances or automobiles.

[0040] For example, ABS alloy materials are used in the preparation of kitchen appliances, medical equipment, sanitary ware and other materials.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] The ABS alloy material provided by the present invention is prepared by selecting appropriate mass parts of components to cooperate with each other, so that the ABS alloy material can be prepared into a thin-walled product with a V0 flame retardant grade and has good rigidity and toughness balance and excellent solvent resistance; specifically, the obtained products can meet the 2.0mm V0 flame retardant grade, the modulus of the product is above 1623MPa, and the impact strength is 14.2kJ / m 2 The above results show that the glacial acetic acid cracking time is above 17 minutes. In addition, the preparation method of the product provided by the present invention is simple to operate and is conducive to actual production. DETAILED DESCRIPTION

[0043] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0044] Unless otherwise specified, the reagents, methods and equipment used in the present invention are all conventional reagents, methods and equipment in the art; and unless otherwise specified, the raw materials used in parallel experiments are from the same batch of raw materials.

[0045] ABS-1: ABS HS3302, rubber content 23%, Mitsubishi Chemical Corporation, Japan;

[0046] ABS-2: ABSDG-417, rubber content 18%, Tianjin Dagu Chemical Co., Ltd.;

[0047] ABS-3: ABS 745N, rubber content 28%, Kumho Petrochemical Co., Ltd., South Korea;

[0048] ASA rubber powder 1: XC-500A, acrylate content 50w.t.%, Kumho Petrochemical Co., Ltd., South Korea;

[0049] ASA rubber powder 2: EM500, acrylate content 70w.t.%, Dongguan Huiyi Chemical Materials Co., Ltd.;

[0050] Phosphorus flame retardant 1: bisphenol A-bis(diphenyl phosphate), commercially available;

[0051] Phosphorus flame retardant 2: triphenyl phosphate, commercially available;

[0052] Nitrogen flame retardant 1: melamine cyanurate, commercially available;

[0053] Nitrogen flame retardant 2: dicyandiamide, commercially available;

[0054] Heteropolyacid salt 1: sodium dodecatungstate phosphate, commercially available;

[0055] Heteropolyacid salt 2: sodium dodecamolybdate phosphate, commercially available;

[0056] Heteropoly acid salt 3: sodium dodecamolybdate silicate, commercially available;

[0057] Compatibilizer 1: KT-2, maleic anhydride grafted ABS, Shenyang Ketong Plastic Technology Co., Ltd.;

[0058] Compatibilizer 2: SMA 700, styrene-maleic anhydride copolymer, Shanghai Huawen Electronic New Materials Co., Ltd.;

[0059] Compatibilizer 3: pentaerythritol monostearate, commercially available;

[0060] Antioxidant: Hindered amine antioxidant, commercially available;

[0061] Lubricant: Stearic acid amide lubricant, commercially available.

[0062] The antioxidants and lubricants used in the parallel experiments of the embodiments and comparative examples were consistent.

[0063] Examples 1-13 and Comparative Examples 1-8

[0064] The embodiments of the present invention and the comparative examples provide an ABS alloy material, and the component contents (parts by weight) of the ABS alloy material are shown in Table 1-2;

[0065] Table 1

[0066]

[0067]

[0068] Table 2

[0069]

[0070] The preparation method of the ABS alloy material provided in Example 1 is:

[0071] The dried raw materials are weighed, mixed and sent into a twin-screw extruder, and subjected to extrusion, strand drawing, cooling, pelletizing and drying to obtain an ABS alloy material;

[0072] Among them, the parameters of the twin-screw extruder are: the aspect ratio of the twin-screw extruder is 40:1, the screw speed is 280rpm, and the temperatures of each section of the screw from the feeding port to the die are 190°C, 190°C, 195°C, 195°C, 195°C, 200°C, and 200°C respectively.

[0073] The preparation methods of the ABS alloy materials provided in Examples 2-13 and Comparative Examples 1-8 are consistent with that in Example 1, except that no relevant components are added.

[0074] Effect example

[0075] The effect examples of the present invention verify the performance of the products prepared in the embodiments and comparative examples; the test items include the following aspects:

[0076] 1. Flame retardant performance: The test standard refers to "UL 94-2018 Flammability Test for Equipment and Appliance Component Materials", and the sample thickness is 2.0mm;

[0077] 2. Izod notched impact strength: the test standard refers to "ISO 180-2000 Determination of IZOD impact strength of plastics";

[0078] 3. Flexural modulus: The test standard refers to "ISO 178-2010 Determination of flexural properties of plastics";

[0079] 4. Solvent resistance: The mold used for solvent resistance test is a steel mold with an inner length of 165mm; Sample: A tensile spline made according to ISO527-1:2019 standard, with a length of 169mm and a curvature of 0.5%; Chemical reagent: glacial acetic acid; Evaluation method: The chemical reagent is evenly applied on the upper surface of the spline at the highest point of the spline bend, and then the time when the spline breaks is recorded as the material chemical resistance evaluation standard.

[0080] The test results are shown in Table 3;

[0081] Table 3

[0082]

[0083]

[0084] It can be seen from Table 3 that when the technical solution of the present invention is adopted, the obtained products have excellent mechanical properties, flame retardant properties and solvent resistance; specifically, the obtained products can meet the 2.0mmV0 flame retardant grade, the modulus of the product is above 1623MPa, and the impact strength is 14.2kJ / m 2 Above, the glacial acetic acid cracking time is more than 17 minutes;

[0085] It can be seen from Examples 1-3, Comparative Example 2 and Comparative Examples 7-8 that the mass fraction of the components has a significant effect on the performance of the product. When the amount of ASA rubber powder added in Comparative Example 2 is too much, the flame retardant performance of the obtained product is significantly reduced, the 2.0 mm flame retardant V0 is not reached, and the modulus of the obtained product also shows a significant downward trend; when the amount of heteropolyacid salt added in Comparative Example 7 is too much, the impact strength of the obtained product shows a significant downward trend; when the amount of compatibilizer added in Comparative Example 8 is too much, the flame retardancy of the obtained product is significantly reduced, and the modulus and impact strength of the product also show a certain downward trend;

[0086] It can be seen from Example 1, Examples 6-7 and Comparative Example 1 that the mass ratio between ASA rubber powder and ABS resin affects the performance of the product. When no ASA rubber powder is added in Comparative Example 1, the flame retardancy of the obtained product is not only reduced, but also unable to meet the 2.0mmV0 flame retardancy grade. The impact strength of the obtained product is also significantly reduced. When the mass ratio of ABS resin and ASA rubber powder is further selected within the preferred range of the present invention, the comprehensive performance of the obtained product is more excellent. Specifically, the obtained product can meet the 2.0mmV0 flame retardancy grade, and the glacial acetic acid cracking time is more than 20min, the modulus of the product is more than 2013MPa, and the impact strength is 15.7kJ / m 2 above;

[0087] It can be seen from Example 1 and Comparative Examples 3-6 that the heteropoly acid salt, phosphorus-based flame retardant and nitrogen-based flame retardant added in the present invention have a certain compounding effect. When any one of them is not added, the flame retardant properties of the obtained product are significantly reduced.

[0088] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. An ABS alloy material, characterized in that: The ABS alloy material comprises the following components in parts by mass: 58-82 parts of ABS resin, 18-42 parts of ASA rubber powder, 6-14 parts of phosphorus flame retardant, 5-11 parts of nitrogen flame retardant, 5-11 parts of heteropoly acid salt, and 2-8 parts of compatibilizer.

2. The ABS alloy material according to claim 1, characterized in that: The mass ratio of the ABS resin to the ASA rubber powder is 1:(0.2-0.7).

3. The ABS alloy material according to claim 1, characterized in that: The heteropolyacid salt includes at least one of dodecamolybdate phosphate, dodecatungstate phosphate, dodecamolybdate silicate and dodecatungstate silicate.

4. The ABS alloy material according to claim 1, characterized in that: The compatibilizer includes at least one of ABS grafted with maleic anhydride, styrene-maleic anhydride grafted product, maleic anhydride grafted with SEBS, and stearic acid alcohol ester.

5. The ABS alloy material according to claim 1, characterized in that: The rubber mass percentage of the ABS resin is 15-30%.

6. The ABS alloy material according to claim 1, characterized in that: The phosphorus-based flame retardant includes at least one of bisphenol A-bis(diphenyl phosphate), triphenyl phosphate, and phenylene tetraphenyl bisphosphate.

7. The ABS alloy material according to claim 1, characterized in that: The nitrogen-based flame retardant includes at least one of melamine urate and dicyandiamide.

8. The ABS alloy material according to claim 1, characterized in that: The ABS alloy material also includes 0.1-1 part of antioxidant and 0.1-1 part of lubricant.

9. The method for preparing the ABS alloy material according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: mixing the components, melting and extruding them to obtain an ABS alloy material.

10. Application of the ABS alloy material according to any one of claims 1 to 8 in the field of household appliances or automobiles.

Citation Information

Patent Citations

  • Flame-retardant ABS composite material and preparation method thereof

    CN118406345A

  • Halogen free flame resistant ABS composition with low cost and high performance, and preparation method and application thereof

    CN102399412A

  • Heat-resistant, halogen-free and flame-retardant ABS (acrylonitrile butadiene styrene) resin composite and preparation method thereof

    CN102690491A

  • Halogen-free flame-retardant ABS composite material as well as preparation method and application thereof

    CN117924872A